Inhibition of the C-X-C Motif Chemokine 12 (CXCL12) and Its Receptor CXCR4 Reduces Utero-Placental Expression of the VEGF System and Increases Utero-Placental Autophagy - Ashley, Ryan L.; Runyan, Cheyenne L.; Maestas, Marlie M.; Trigo, Elisa; Silver, Gail (Frontiers in Veterinary Science, 2021)
The placenta, a unique organ that only develops during pregnancy, is essential for nutrient, oxygen, and waste exchange between offspring and mother. Yet, despite its importance, the placenta remains one of the least understood organs and knowledge of early placental formation is particularly limited. Abnormalities in placental development result in placental dysfunction or insufficiency whereby normal placental physiology is impaired. Placental dysfunction is a frequent source of pregnancy loss in livestock, inflicting serious economic impacts to producers. Though the underlying causes of placental dysfunction are not well characterized, initiation of disease is thought to occur during establishment of functional fetal and placental circulation. A comprehensive understanding of the mechanisms controlling placental growth and vascularization are necessary to improve reproductive success in livestock. We propose chemokine C-X-C motif ligand 12 (CXCL12) signaling through its receptor CXCR4 functions as a chief coordinator of vascularization through direct actions on fetal trophoblast and maternal endometrial and immune cells. To investigate CXCL12-CXCR4 signaling on uteroplacental vascular remodeling at the fetal-maternal interface we utilized a CXCR4 antagonist (AMD3100). On day 12 post-breeding in sheep, osmotic pumps were surgically installed and delivered either AMD3100 or saline into the uterine lumen ipsilateral to the corpus luteum for 14 days. On day 35 of ovine pregnancy, fetal/placental and endometrial tissues were collected, snap-frozen in liquid nitrogen, and uterine horn cross sections preserved for immunofluorescent analysis. Suppressing CXCL12-CXCR4 at the fetal-maternal interface during initial placental vascularization resulted in diminished abundance of select angiogenic factors in fetal and maternal placenta on day 35. Compared to control less vascular endothelial growth factor (VEGF), and VEFG receptor 2 (KDR) was observed in endometrium when CXCL12-CXCR4 was diminished. Less VEGF was also evident in fetal placenta (cotyledons) in ewes receiving AMD3100 infusion compared to control. Suppressing CXCL12-CXCR4 at the fetal-maternal interface also resulted in greater autophagy induction in fetal and maternal placenta compared to control, suggestive of CXCL12-CXCR4 impacting cell survival. CXCL12-CXCR4 signaling may govern placental homeostasis by serving as a critical upstream mediator of vascularization and cell viability, thereby ensuring appropriate placental development.